The Impact of Banathy Instructional Design Model and Motivation on Science Learning Outcomes in Fourth-Grade Students - Susi Angraini; Darmansyah; Alwen Bentri; Zuwirna (Jurnal Penelitian Pendidikan IPA, 2025)
This study addresses the problem of low science learning outcomes among elementary students by examining whether the Banathy Instructional Design Model can improve performance across different motivation levels. The objective was to compare the effects of the Banathy model and conventional instruction on fourth-grade students’ science learning outcomes while also analyzing the interaction between instructional model and student motivation. A quasi-experimental design with a nonequivalent control group was employed, involving one experimental group taught using the Banathy model and one control group receiving conventional instruction. Data on learning outcomes were collected through a standardized posttest and analyzed using comparative statistical techniques. The results show that students in the experimental group achieved significantly higher science learning outcomes than those taught conventionally. Further analysis indicates that the Banathy model benefits both high- and low-motivation students, although highly motivated students demonstrate the greatest improvement. Notably, even students with lower motivation exhibited better performance when taught using the Banathy model. These findings suggest that the Banathy Instructional Design Model is effective for heterogeneous classrooms and can enhance science learning outcomes regardless of students’ initial motivation levels.